Occurrence and path pollution of emerging organic contaminants in mineral water of Hranice hypogenic Karst - Oppeltová, Petra; Vlček, Vítězslav; Geršl, Milan; Chaloupský, Pavel; Ulrich, Ondřej; Sedláček, Jozef; Vavrouchová, Hana; Kohoutková, Kristýna; Klepárník, Radim; Šimečková, Jana (Frontiers in Environmental Science, 2024)
The Hranice hypogenic karst region includes urban, spa and agricultural areas and industry complexes that affect water quality in the region. Emerging organic contaminants (EOCs), especially pesticides and pharmaceuticals, are released into the complex aquatic system. These substances and their metabolites can affect aquatic and human life, as well as the regional development of the wider area traditionally associated with the spa. In this study, we conducted preliminary screening for pesticides and pharmaceuticals at 33 sampling sites and across different location types, including surface water, drainage water, a shallow well, groundwater and thermal karst water. Sampling occurred between February 2022 and June 2023. The results generally confirm that current land use is causing pollution in the karst system. The monitored substances were present in all water types, and in most cases the concentrations of pesticides were lower than those of their metabolites.Chloridazon desphenyl (DESPH) is the most widespread pesticide in surface, ground and hypogenic waters. Its concentrations in surface waters were 5.7 ng•L -1 -2230 ng•L -1 , in groundwaters were 11.3 ng•L -1 -1490 ng•L -1 and in karst hypogenic waters 5.4 ng•L -1 -378 ng•L -1 . Diclofenac was the most widespread substance from the pharmaceutical group. Its concentrations ranged from 5.6 ng•L -1 -549 ng•L -1 in surface waters, 8.4 ng•L -1 -112 ng•L -1 in groundwaters and 5.1 ng•L -1 -47.4 ng•L -1 in karst hypogenic waters. Directly in the karst hypogenic waters, the following EOCs were repeatedly detected: atrazine and its metabolites, simazin, metazachlor ethane sulfonic acid (ESA), metolachlor ESA, alachlor ESA, chloridazon DESPH, diclofenac, ibuprofen, azithromycin, bisphenol A and diethyltoluamide (DEET).The initial research hypothesis is that hydrothermal karst waters are of sub-recent age and deep circulation and, unlike surface and groundwaters, are not contaminated by recent pollutants. A certain component of these waters is therefore a shallow and shorter circulation.